Synergistic Interplay of Medicinal Chemistry and Formulation Strategies in Nanotechnology - From Drug Discovery to Nanocarrier Design and Development - Sunoqrot, Suhair; Hamed, Rania; Abdel-Halim, Heba; Tarawneh, Ola (Current Topics in Medicinal Chemistry, 2017)
Over the last few decades, nanotechnology has given rise to promising new therapies and diagnostic tools for a wide range of diseases, especially cancer. The unique properties of nanocarriers such as liposomes, polymeric nanoparticles, micelles, and bioconjugates have mainly been exploited to enhance drug solubility, dissolution, and bioavailability. The most important advantage offered by nanotechnology is the ability to specifically target organs, tissues, and individual cells, which ultimately reduces the systemic side effects and improves the therapeutic index of drug molecules. The contribution of medicinal chemistry to nanotechnology is evident in the abundance of new active molecules that are being discovered but are faced with tremendous delivery challenges by conventional formulation strategies. Additionally, medicinal chemistry plays a crucial role in all the steps involved in the preparation of nanocarriers, where structure-activity relationships of the drug molecule as well as the nanocarrier are harnessed to enhance the design, efficacy, and safety of nanoformulations. The aim of this review is to provide an overview of the contributions of medicinal chemistry to nanotechnology, from supplying drug candidates and inspiring high-throughput nanocarrier design strategies, to structure-activity relationship elucidation and construction of computational models for better understanding of nanocarrier physicochemical properties and biological behavior. These two fields are undoubtedly interconnected and we will continue to see the fruits of that communion for years to come.
Keywords: Drug discovery